Pengaruh Pemberian Trichoderma sp. sebagai Dekomposer Berbagai Kotoran Ternak Terhadap Lama Pengomposan dan Kualitas Kompos yang Dihasilkan - Ismil Arum Fitri Asih; Ahmad Ilham Tanzil; Ummi Sholikhah; Wildan Muhlison (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
Livestock farming is one of the contributors to the amount of organic waste with the most dominant being solid manure. This livestock waste can be used as solid organic fertilizer, because it contains nutrients that are good for plants, namely nitrogen, phosphorus and potassium. This composting is carried out by adding Trichoderma sp. as the decomposer. This research was conducted to determine the effect of giving Trichoderma sp. and differences in raw materials on the quality of organic fertilizer produced and the length of composting. This research was carried out from February – September 2024, in the Greenhouse and Soil Chemistry Laboratory, Faculty of Agriculture, Jember University. using a factorial RAL (Completely Randomized Design) experimental design, namely the influence of different types of livestock manure and the addition of Trichoderma sp. fungus decomposer, with 6 treatments repeated 4 times so that there were 24 experimental units. The results showed a reduction in weight, a change in pH approaching neutral, and a temp erature equivalent to groundwater temperature. Giving Trichoderma sp. causes a color difference in organic fertilizer made from goat manure, but does not make a difference in organic fertilizer made from chicken manure and cow manure. The texture of the fertilizer produced is crumbly with an aroma resembling soil. Based on physical quality, the organic fertilizer that meets the standards first is organic fertilizer made from goat manure with the addition of Trichoderma sp. The best compost quality is owned by the B2D1 treatment (livestock manure with the addition of Trichoderma sp.) because it meets the standards of SNI Kompos Nomor 19-7030-2004 and Permentan No.70 Tahun 2011 concerning organic fertilizer in the variables N, P, K, dan C-Organic